Photoinduced Intra- and Intermolecular Energy Transfer in Chlorophyll a Dimer - Zheng, Fulu (2017)
Applying nonadiabatic excited-state molecular dynamics, we investigate excitation energy transfer and exciton localization dynamics in a chlorophyll a (Chla) dimer system at the interface of two monomers of light-harvesting complex II trimer. After its optical excitation at the red edge of the Soret (B) band, the Chla dimer experiences an ultrafast intra- and intermolecular nonradiative relaxation process to the lowest band (Qy). The energy relaxation is found to run faster in the Chla dimer than in the Chla monomer. Once the molecular system reaches the lowest Qy band composed of two lowest excited states S1 and S2, the concluding relaxation step involves the S2 → S1 population transfer, resulting in a relatively slower relaxation rate. The strength of thermal fluctuations exceeds intraband electronic coupling between the states belonging to a certain band (B, Qx, and Qy), producing localized states on individual chromophores. Therefore, time evolution of spatial electronic localization during internal conversion reveals transient trapping on one of the Chla monomers participating in the events of intermonomeric energy exchange. In the phase space domains where electronic states are strongly coupled, these states become nearly degenerate promoting Frenkel-exciton-like delocalization and interchromophore energy transfer. As energy relaxation occurs, redistribution of the transition density on two Chla monomers leads to nearly equal distribution of the exciton among the molecules. For a single Chla, our analysis of excitonic dynamics reveals wave function amplitude transfer from nitrogen and outer carbon atoms to inner carbon atoms during nonradiative relaxation.